Effect of Drying and Storage on Quality of Betel Leaves - Rayaguru, K; Khan, Md. K; Mohanty, S N; Sahoo, G R (Journal of Agricultural Engineering, 2007)
Due to low keeping quality, betel leaves worth millions of rupees go as waste every year. If proper drying methods are scientifically standardized, the leaves can be processed at garden level and the grower can earn more profit. Therefore, the effect of different drying methods namely, sun drying, shade drying, solar drying and mechanical drying, on the quality characteristics of the leaves was evaluated. It was found that shade drying took maximum time for drying and was followed by solar drying, hot air drying (40degree C), sun drying and hot air drying (50degree C). However, maximum nutrient could be preserved in shade drying. The study was also carried out on storage of fresh betel leaves using traditional packaging, polyethylene packaging and ventilated polyethylene packaging. Before storing, the leaves were subjected to chemical treatment (5 ppm benzyl adenine, 8 h) and heat treatment (45degree C, 1 h). It was observed that the shelflife of the leaves stored by various methods ranged between 12 and 21 days in winter and 4 to 12 days in summer. The leaves subjected to heat treatment in traditional packaging showed better performance.